Implementation of a Hybrid Cryptosystem Using ChaCha20 and ECC for Image Encryption in an Android Application - Zai, Samuel Anaya Putra; Debi Yandra Niska; Zulfahmi Indra; Kana Saputra; Adidtya Perdana (Politeknik Ganesha Medan, 2025)
This study aims to develop an Android application capable of securely encrypting and decrypting images using a hybrid cryptographic method. The system combines the ChaCha20 algorithm as symmetric cryptography to encrypt image files, and Elliptic Curve Cryptography (ECC) as asymmetric cryptography to encrypt the ChaCha20 key. The key used is temporary (ephemeral), ensuring that only the intended recipient who possesses the appropriate ECC private key can decrypt the file. The application was developed using the Kotlin programming language in Android Studio, with a PHP-based backend and MySQL database. Testing was conducted using the black-box method and involved 15 beta testers to evaluate functionality, security, and usability aspects. The results show that all features of the application run properly, and the encryption and decryption processes can be performed efficiently and securely. Beta testers gave an average rating of 4.6 out of 5 and stated that the application is easy to use and provides sufficient protection for personal data. Therefore, the developed application successfully meets the objectives of the study and offers an alternative solution for securing image file transfers between users via Android devices.